2020
DOI: 10.1111/1471-0528.16250
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age and high‐risk human papillomavirus (hrHPV) status on the prevalence of high‐grade cervical intraepithelial neoplasia (CIN2+) in women with persistent hrHPV‐positive, cytology‐negative screening samples: a prospective cohort study

Abstract: Objective To establish the prevalence of high‐grade cervical intraepithelial neoplasia (CIN2+) in women referred to colposcopy with persistent high‐risk human papillomavirus (hrHPV) cytology‐negative screening sample according to hrHPV genotype, age at referral and colposcopic performance. Design Prospective cohort study. Setting Single colposcopy clinic linked to a population‐based screening programme. Population Women referred with persistent hrHPV cytology‐negative routine screening samples. Methods Prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(34 citation statements)
references
References 28 publications
4
28
0
Order By: Relevance
“…This was a service evaluation carried out in the Jessop Wing Colposcopy clinic and so no ethical approval was required [ 6 ]. All patient data was anonymised.…”
Section: Methodsmentioning
confidence: 99%
“…This was a service evaluation carried out in the Jessop Wing Colposcopy clinic and so no ethical approval was required [ 6 ]. All patient data was anonymised.…”
Section: Methodsmentioning
confidence: 99%
“…Oral contraceptive use has been reported to increase the risk of developing cervical cancer in women with normal cytology in a retrospective population-based cohort study [30]. Recently, a UK prospective cohort study found that the progression probability of normal cervical cytology to CIN2+ decreased with age, with the highest in the 25-34 years old population [31].…”
Section: Discussionmentioning
confidence: 99%
“…5 As several studies have demonstrated that HPV-based screening is associated with a significantly higher sensitivity for cervical intraepithelial neoplasia grade 2 or worse (CIN2+) detection compared with screening with cytology, many European countries have either switched to or plan to implement HPV-based screening. 12,14 However, the sensitivity of HPVbased screening has also been reported to decline with age. 12 Whether this is explained by sampling issues or because older women are more likely to be diagnosed with an HPV-negative cancer 15 compared with younger women remains unclear.…”
Section: F I G U R Ementioning
confidence: 99%
“…A previous US study reported that 19% of cervical cancer cases were HPV negative and 5.5% were cotest negative (ie cytology and HPV), with older women more likely to test HPV-negative as compared with younger women. 16 As most newly detected HPV infections are transient and are associated with a low risk of CIN2+, 12,14 it is important to apply a triage strategy to identify women at increased risk who area in need of referral to colposcopy, thereby reducing the number of unnecessary colposcopies. Triage of HPV-positive women is typically performed with cytology and/or partial or complete HPV genotyping; however, given the low sensitivity of cytology in older women and the low proportion of HPV16/18-positive cancers among older women, 17 triage by cytology and partial genotyping may not be the best strategies in older women.…”
Section: F I G U R Ementioning
confidence: 99%
See 1 more Smart Citation